The First American Scoop: The Pedra Furada Controversy in Newspapers (1978–2015). (August 2016) - Carandell Baruzzi, Miquel
Abstract: In July 1986, the cover of Nature featured rock paintings from the Pedra Furada rock shelter in the Serra da Capivara National Park in Brazil. In that issue, Niède Guidon, head of the excavations at Pedra Furada, co‐authored an article that pushed back the arrival of the first humans to South America to 32, 000 years ago. This controversial claim was widely reported by newspapers in Brazil and in other countries like the USA. Using this case, this paper aims to shed light on the role of newspapers in prehistory in three different ways. Firstly, it will analyze how Guidon's early outreach effort helped to transform the Serra da Capivara research into a well‐known scientific project in Brazil – a project that tried to protect and economically promote this area, promoting at the same time the disputed claims. Secondly, this paper will highlight how Guidon's research adapted to the logic of the media by using the rock paintings at Pedra Furada as 'legitimators' of the idea of an early human presence in the shelter. And thirdly, this paper will emphasize how newspapers became the platform for the scientific debate that took place before, during and after the discussion in more traditional scientific media. All this will help to provide insight into how newspapers became a crucial agent in the construction of late 20th century prehistoric knowledge.